Final report for industrial attachment with Ching Soon Construction Pte Ltd - Chua, Heng Choon. (2008)
The main objective of this attachment with Ching Soon Construction Pte. Ltd. are to gain the first hand experience in piling profession and to apply the acquired knowledge in piled foundation design and analysis.